Prediction of temperature distribution during flashover caused by backdraft fire - Lim, Shi Han (2016)
The effect of ventilation on fire development is one of the most important phenomena to understand modern compartment fire behavior, causing fire behavior shifted from traditional fire behavior to modern fire behavior. Ventilation controls the growth of the fire process and this creates problem in describing fire activities in some ways posing potential hazards to firefighters during fire ground. Backdraft is one of the most deadly fire phenomena in a ventilation limiting building. Backdraft develops from an oxygen starved fire and yet, continue to produce a fuel-rich environment in the compartment. If an opening is made and fresh air is allow to enter the compartment, high temperature hot gases remained in the compartment will rapidly burn once in contact with the incoming fresh air, resulting a fireball associated with a blast wave. Identifying factors that contribute to this extreme fire phenomenon is important. In this paper, a meta analysis of results from related multiple studies to understand and to analyze the meaning of the results obtained of a collection of studies The effect of varying the ventilation by means of changing different geometries of the openings, the location of ignition source, and the mass fraction of unburned gas are discussed. The results acquired from the meta analysis have shown that the smaller the change of the geometry of the opening, the further the location of ignition source from the opening of the compartment and when the mass fraction of unburned fuel remained in the compartment exceeds a certain critical value, the easier for the backdraft to occur. In addition, the analysis also show that the key parameter determining the backdraft occurrence is the mass fraction of unburned fuel, followed by the ventilation condition.